2004
DOI: 10.1387/ijdb.041844vp
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of early chick embryo morphogenesis by insulin is associated with altered expression of embryonic genes

Abstract: In the present study, we show that insulin accelerates early morphogenesis in gastrulating chick embryo explants cultured in vitro, whereas antiserum to insulin adversely affects this process. Comparison between length of body axis of control and treated embryos clearly brings out the significant acceleration of development by excess insulin (0.175 to 17.5 nM). In embryos treated with 87.5 and 175 nM insulin, a high occurrence of abnormalities is observed. Treatment of embryos with antiserum to porcine insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…5) [51]. In parallel to this major role in survival/death control, insulin and proinsulin may also play a role in early morphogenesis and cardiogenesis [69,73,74]. Moreover, human fetuses lacking insulin receptor are significantly growth-retarded, showing a stronger phenotype than the insulin receptor knockout mouse (reviewed in [75]).…”
Section: Biological Functions Of Proinsulin/insulin In Early Developmentmentioning
confidence: 99%
“…5) [51]. In parallel to this major role in survival/death control, insulin and proinsulin may also play a role in early morphogenesis and cardiogenesis [69,73,74]. Moreover, human fetuses lacking insulin receptor are significantly growth-retarded, showing a stronger phenotype than the insulin receptor knockout mouse (reviewed in [75]).…”
Section: Biological Functions Of Proinsulin/insulin In Early Developmentmentioning
confidence: 99%
“…Glucose was found to readily enter the cells of the heart of 5-6 day chicken embryo, in which the uptake of 2-deoxyglucose was stimulated by physiological levels of insulin as early as 5-6 days (Kutchai et al, 1977). It has been shown that insulin has a considerable role in chicken early-embryonic morphogenesis with expression changes in the involved genes (Patwardhan et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…A range of signaling molecules and their roles have been implicated in vertebrate development (Borgave and Ghaskadbi, 2009; SanchezCalderon et al, 2007;Patwardhan et al, 2004;Waschek et al, 1998;Hallbook et al, 1995;Ernfors et al, 1995;Hyuga et al, 1993). Thyroid hormones are known to play an important role in the early development including neurulation of several vertebrates and previous studies have shown the occurrence of enzymes that are involved in the recycling of Iodine from thyroid hormones (Courtin et al, 2005;Gereben et al, 2004;Geyten et al, 2002;Asteria, 1998;Becker et al, 1997;Rosenkilde and Ussing, 1996).…”
Section: Abstract: Chick Embryo Gastrulation Immunocytochemistry mentioning
confidence: 99%